"Cell Migration" Is the Ontology Group Differentially Expressed in Porcine Oocytes Before and After In Vitro Maturation: A Microarray Approach - Kranc, Wiesława; Budna, Joanna; Chachuła, Adrian; Borys, Sylwia; Bryja, Artur; Rybska, Marta; Ciesiółka, Sylwia; Sumelka, Ewa; Jeseta, Michał; Brüssow, Klaus P; Bukowska, Dorota; Antosik, Paweł; et al. (DNA and cell biology, 2017)
Maturation of cumulus-oocyte complexes (COCs) is crucial for further successful monospermic fertilization, embryo growth, and implantation. All these events are accompanied by proliferation and differentiation of cumulus cells. The migration of COCs to the oviduct after ovulation and the interaction between female gametes and/or embryos with maternal tissues are still poorly recognized on the molecular level. This study was aimed to first demonstrate the mRNA expression profile of cell migration markers during different stages of porcine oocytes maturation and developmental capability in vitro. The COCs were collected from a total of 45 pubertal crossbred Landrace gilts, brilliant cresyl blue (BCB) stained, and analyzed before (n = 150) or after (n = 150) in vitro maturation (IVM). Using the Affymetrix® Porcine Gene 1.1 ST Array, the expression profile of 12,258 porcine transcripts was examined. We found nine genes involved in cell migration mechanisms, that is, PLD1, KIT, LAMA2, MAP3K1, VEGFA, TGFBR3, INSR, TPM1, and RTN4. These genes were upregulated in porcine oocytes before IVM as compared with post-IVM expression analysis. Moreover, important mechanisms of biological interaction between VEGFA-KIT and VEGFA-INSR were also observed. The upregulation and/or downregulation of selected mRNAs expression after microarray assays was checked and approved by real-time quantitative polymerase chain reaction. We suggest that several genes, including LAMA2 or TPM1, encode proteins participating in the formation of the oocyte's protein architecture such as microtubules and kinetochore reorganization. As the expression of all "migration regulatory genes" investigated in this study was significantly upregulated in oocytes before IVM, we conclude that they may contribute to the maturational capability of porcine oocytes. However, migration potency of COCs is not accompanied by achievement of the MII stage by porcine oocytes in vitro. The investigated genes such as PLD1, KIT, LAMA2, MAP3K1, VEGFA, TGFBR3, INSR, TPM1, and RTN4 may be recognized as a new marker of porcine oocytes maturational competence during in vitro culture.
Keywords: genová ontologie; Animals; Oligonucleotide Array Sequence Analysis; Gene Ontology; Female; Oogenesis; cell migration; IVM techniky; oogeneze; ženské pohlaví; Oocytes; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; oocyty; prasata; stanovení celkové genové exprese; In Vitro Oocyte Maturation Techniques; pohyb buněk; Swine; pig; transkriptom; Cell Movement; zvířata; oocyte; Transcriptome; Gene Expression Profiling; microarray